ANALYSIS OF DETERMINATION OF THE IMPLEMENTATION ACCRUAL-BASED ACCOUNTING STANDARDS IN LHOKSEUMAWE REGENCY - Yusra, Muhammad; Afni Yunita , Nur (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2021)
Implementation of Government Regulation Number 71 of 2010 concerning Government Accounting Standards brought changes in the presentation of government financial statements, which previously used cash-based accounting standards, to accrual-based accounting standards. Cash-based recognizes the recording of transactions and recognition occurs only when cash is out and cash in and does not record liabilities and assets at all. Accrual-based recording is believed to be able to produce financial reports that are more accurate and more reliable, comprehensive and relevant for decision making. In order to support the implementation of a good and competent accrual basis, supporting factors are needed such as human resources, organizational commitment, utilization of information and communication technology. The purpose of this study was to analyze the influence of human resources, organizational commitment, information and communication technology on the application of accrual-based accounting standards in the Lhokseumawe regency. The number of respondents in this study were 68 employees from the SKPK in Lhokseumawe regency, the research data was in the form of primary data with data analysis using multiple linear regression. The results showed that human resources, government commitment, information technology, and communication had an effect on the application of accrual-based accounting standards in Lhokseumawe regency. The number of respondents in this study were 68 employees from the SKPK in Lhokseumawe regency, the research data was in the form of primary data with data analysis using multiple linear regression. The results showed that human resources, government commitment, information technology, and communication had an effect on the application of accrual-based accounting standards in Lhokseumawe regency. The number of respondents in this study were 68 employees from the SKPK in Lhokseumawe regency, the research data was in the form of primary data with data analysis using multiple linear regression. The results showed that human resources, government commitment, information technology, and communication had an effect on the application of accrual-based accounting standards in the Lhokseumawe regency.